Are Perioperative Bundles Associated With Reduced Postoperative Morbidity in Women Undergoing Benign Hysterectomy? Retrospective Cohort Analysis of 16, 286 Cases in Michigan. Issue 5 (May 2017) - Harris, John A.; Sammarco, Anne G.; Swenson, Carolyn W.; Uppal, Shitanshu; Kamdar, Neil; Campbell, Darrel; Evilsizer, Sarah; DeLancey, John O.; Morgan, Daniel M.
Abstract : (Abstracted from Am J Obstet Gynecol 2017;216:502.e1–502.e11) In the past decade, team-based interventions such as checklists and bundle processes have been shown to improve health care outcomes.